706 Intestinal Epithelial Dysplasia - A Case Report of a Milder Phenotype. (October 2012) - Lesanu, G; Tincu, I; Gherghiceanu, M; Becheanu, C; Dumbrava, M; Pacurar, D; Danila, V
Abstract : The intractable diarrhea of infancy remains a difficult challenge for the pediatrician. We report a rare case of a five-month-old female infant admitted in "Grigore Alexandrescu" Emergency Children's Hospital, Bucharest for diarrheic stools and severe malnutrition with birth onset. She was exclusively breastfed with poor gain weight (360g in 5 months). During the 5 months of life the child was repeatedly admitted to other hospitals because of diarrhea and failure to thrive without a precise diagnosis. We mention that she had a sister who died at 3 months old because of severe diarrhea with birth onset. At admission the infant had severe malnutrition with watery diarrhea and facial dysmorphism. After extensive investigations we excluded infections and allergic causes, cystic fibrosis, immune and autoimmune enterophaty, motility disorders. We performed inferior and superior endoscopies with biopsies that excluded microvillus inclusion disease. Examination of the biopsy specimens (optic and electronic microscopy) revealed the diagnosis of intestinal epithelial dysplasia (IED). The patient received parenteral and enteral nutrition with elemental formulas. Previous reports have suggested that IED may be a congenital inherited autosomal recessive disease. We report a case of congenital enteropathy that represents a diagnostic and therapeutically challenge.